Fenomena LGBT Di Pondok Pesantren X Kabupaten Lamongan - Siti Maisaroh; Siti Nur Hasanah; Andhita Risko Faristiana (Universitas Katolik Widya Karya Malang, 2023)
A phenomenon in Islamic boarding schools which has recently emerged to the surface, raises competition regarding the existence of a group. This group is called LGBT, in terms of sexual behavior that is not in general and is not common in the Islamic boarding school environment which upholds the Islamic religion. Therefore, this study aims to provide views from an Islamic religious, social, and health perspective on the LGBT phenomenon. The research method used is a qualitative descriptive approach with a phenomenological strategy. Research information includes observations of the author, LGBT individuals, in-depth interviews with his fellow students and analysis of documents. The results of the study show that religion views LGBT as deviant behavior that is not in accordance with Islamic religious principles. Many internal factors that influence a person to become LGBT are internal factors that are more dominant. The Islamic religion does not want this behavior by referring to the holy book and hadiths that marriage can only be carried out by a man and a woman, and if it deviates it is a big sin. On the other hand, there are efforts to restrain them from returning to their nature so that true human dignity and dignity are maintained and Islamic harmony with Islamic boarding school education.